Offset-free feedback linearisation control of a three-phase grid-connected photovoltaic system - Errouissi, R.; Al-Durra, A.; Muyeen, S.M. (The Institution of Engineering and Technology, 2016)
In this study, a state feedback control law is combined with a disturbance observer to enhance disturbance rejection capability of a grid-connected photovoltaic (PV) inverter. The control law is based on input-output feedback linearisation technique, while the existing disturbance observer is simplified and adopted for the system under investigation. The resulting control law has a proportional-integral (PI)/almost PI-derivative-like structure, which is convenient for real-time implementation. The objective of the proposed approach is to improve the DC-bus voltage regulation, while at the same time control the power exchange between the PV system and the grid. The stability of the closed-loop system under the composite controller is guaranteed by simple design parameters. Both simulation and experimental results show that the proposed method has significant abilities to initiate fast current control and accurate adjustment of the DC-bus voltage under model uncertainty and external disturbance.